2021
DOI: 10.3389/fpubh.2021.596938
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning Information for Severe and Critical Patients With COVID-19 Based on Quantitative CT Analysis of Lung Segments

Abstract: Background: The coronavirus disease 2019 (COVID-19) outbreak is spreading rapidly around the world.Purpose: We aimed to explore early warning information for patients with severe/critical COVID-19 based on quantitative analysis of chest CT images at the lung segment level.Materials and Methods: A dataset of 81 patients with coronavirus disease 2019 (COVID-19) treated at Wuhan Wuchang hospital in Wuhan city from 21 January 2020 to 14 February 2020 was retrospectively analyzed, including ordinary and severe/crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…We also observed higher levels of α2,6-sialic acid in the lower lobe of the lungs in patients who have died from COVID-19. In previous studies, CT scans showed that lower lobe involvement and consolidation is common in COVID-19 patients 76, 77 . In the lower lobe, staining for α2,6-sialic acid appeared strongest at the barrier of blood-gas exchange.…”
Section: Discussionmentioning
confidence: 88%
“…We also observed higher levels of α2,6-sialic acid in the lower lobe of the lungs in patients who have died from COVID-19. In previous studies, CT scans showed that lower lobe involvement and consolidation is common in COVID-19 patients 76, 77 . In the lower lobe, staining for α2,6-sialic acid appeared strongest at the barrier of blood-gas exchange.…”
Section: Discussionmentioning
confidence: 88%
“…This may be due to the physiologic regional inhomogeneity of the lung as a result of the influence of gravity [ 33 ]. The erect lung is marked by striking regional non-uniformity in perfusion and ventilation resulting in blood flow and ventilation predominating in the lower lobes [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe and critical cases were combined into the same group in this study. We did not consider CT score [ 4 , 5 ] in the classification of COVID-19 severity.…”
Section: Methodsmentioning
confidence: 99%